Chronic obstructive pulmonary disease and the risk of 12 cardiovascular diseases: a population-based study using UK primary care data. Issue 9 (3rd February 2018) - Morgan, Ann D; Rothnie, Kieran J; Bhaskaran, Krishnan; Smeeth, Liam; Quint, Jennifer K
Abstract : Risks for cardiovascular diseases (CVDs) other than myocardial infarction and stroke in the general COPD population are not well quantified. We used a matched cohort study design and Cox regression to estimate relative risks for 12 separate CVDs in a large population-based cohort of patients with COPD over a 12-year period. Associations between COPD and individual CVDs were heterogeneous, with the highest relative risks observed for heart failure and diseases of the arterial circulation (in excess of 2.5 for those aged 64–75 years). Relative risks declined with increasing age but for most CVD outcomes remained unchanged over the study period.